Gastos das famílias brasileiras com transporte urbano público e privado no Brasil: Uma análise da pof 2003 e 2009 - Carlos Henrique R. Carvalho; Rafael Henrique M. Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This text analyzes Brazilian families spending with public and private urban transport based on family budget surveys conducted by IBGE in 2003 and 2009. It was observed that on average Brazilian families spend about 15% of their income on urban transportation. Private transport expenses are about five times greater than spending on public transport, with a growing trend of this difference. The stimulus policies to individual transport coupled with income growth are leading families of all income levels to raise their expenditure on individual transport, intensifying its use in everyday life with a strong impact on the conditions of (general) population mobility. As income increases, the greater the propensity to spend even more on private vehicles. Thus, especially in periods of strong growth in income, we suggest policies for the rational use of individual transport, such as more realistically charging the use of urban space, and also improving the quality of public transport systems, making it more attractive to the general population.
Keywords: R49; 330; transit; private transportation; public transportation; urban transportation spending; Personenverkehr; Stadtverkehr; Verbraucherausgaben; Brasilien